Hypothalamus and amyotrophic lateral sclerosis: potential implications in sleep disorders - Gnoni, Valentina; Zoccolella, Stefano; Giugno, Alessia; Urso, Daniele; Tamburrino, Ludovica; Filardi, Marco; Logroscino, Giancarlo (Frontiers in Aging Neuroscience, 2023)
Amyotrophic lateral sclerosis (ALS) is a devastating neurodegenerative disease that affects both motor and non-motor functions, including sleep regulation. Emerging evidence suggests that the hypothalamus, a brain region that plays a critical role in sleep-wake regulation, may be involved in the pathogenesis of ALS-related sleep disturbances. In this review, we have summarized results of studies on sleep disorders in ALS published between 2000 and 2023. Thereafter, we examined possible mechanisms by which hypothalamic dysfunctions may contribute to ALS-related sleep disturbances. Achieving a deeper understanding of the relationship between hypothalamic dysfunction and sleep disturbances in ALS can help improve the overall management of ALS and reduce the burden on patients and their families.